A review on the protection of timber bridges. Issue 3 (27th May 2018) - Mahnert, Karl-Christian; Hundhausen, Ulrich
ABSTRACT: Wood plays a major role for the Norwegian Public Roads Administration (NPRA) in design and construction of modern bridges. The Norwegian design code demands a service life of 100 years; this poses a challenge independent of the material used. In case of wood, NPRA regards the creosote treatment as crucial to achieve the required service life. Creosote, however, is controversial within the European Commission due to its toxicity and its approval for future use is questionable. This situation calls for evaluating alternative protection measures for timber bridges. The present paper gives an overview of the importance of timber bridge design in Norway, Sweden, Finland, Germany, and the USA and reviews the literature covering protection by design, preservative treatment, wood modification, and monitoring and inspection.